(untitled) (Communication & Society, 2016)
The article analyzes the key ideas that allowed Downton Abbey to become one of the most iconic series in the British landscape. By focusing on the show’s narrative rhetoric, we especially learn about all those aspects that find their roots in American TV shows. Downton Abbey’s creators, producers Gareth Neame and screenwriter Julian Fellowes, asserted that they modeled their show after series like ER and The West Wing. Inspired by the movie Gosford Park, Neame and Fellowes were aiming to reboot the genre of period drama. The article specifically identifies Downton Abbey’s elements of international success in the unity between its procedural arena and characters web as well as in the ability to focus organically on a general theme and to keep its tone emotionally consistent. The article ends by questioning all those lectures that look at Downton Abbey exclusively as an escapist and utopic piece. On the contrary, the article highlights the proactive nature of the show. At its dramatic core, Downton Abbey can be considered very similar to a seemingly different show like The West Wing.